Desenvolvimento e caracterização de iogurte caprino tipo grego potencialmente probiótico adicionado de geleia mista de acerola e morango - Morais, Jéssica Lima de (2021)
Functional foods are increasingly evident in the Brazilian market, with a demand for products that meet consumer demand. The development of products from goat's milk, added to natural components with bioactive compounds, and even microorganisms with probiotic potential such as Limolactobacillus mucosae CNPC007 is shown to be a viable alternative. Strawberry and acerola, as they are very rich in nutrients and with chemical components that have relevant biological activities, are a promising alternative for the development of functional products. Given the above, the objective of this research was to elaborate and characterize the technological and quality aspects, as well as the functional potential of potentially probiotic Greek-type goat yogurt produced with autochthonous adjunct culture Limosilactobacillus mucosae CNP007 added to different concentrations of mixed acerola and strawberry jelly. The yoghurts were prepared using a standardized laboratory methodology. Six yoghurt formulations were prepared and evaluated at times 1, 7, 14, 21 and 28 days of refrigerated storage (4 ± 1 °C), regarding their technological, physical and physicochemical, rheological and microbiological characteristics (viability ); the determination of the chemical profile was carried out at times 1, 14 and 28 days of refrigerated storage, sensory analyzes of purchase intention and acceptance were carried out at times 1 and 28, CATA and JAR scale at time 1 and the protective effect of the food matrix on the survival of lactic acid bacteria under simulated conditions of the gastrointestinal tract (TGI) was done after 7 days of refrigerated storage. The addition of the probiotic strain reduced protein levels and increased proteolysis. However, viscosity and texture significantly improved. The creamier and more viscous texture of the samples added from the probiotic culture can be explained by the effects of the exopolysaccharides produced by the strain. The addition of jelly to formulations containing L. mucosae increased the antioxidant power and reduced the viscosity of yogurt. The reduction in viscosity was probably due to the breakdown of the protein network by fruit enzymes. However, the flavor, aroma, color and global acceptance of the yogurt benefited from the presence of jam, resulting in greater purchase intent. Both the addition of jelly and L. mucosae proved to be beneficial to mask the strong taste of goat milk, positively impacting purchase intent. The food matrix acted as a protector of the L. mucosae strain, regardless of the addition of jelly, allowing it to reach the ileum at viable counts to perform its probiotic function (> 7 log CFU/g). Therefore, the developed goat yogurt has potential for investment in the dairy industry. The typical aroma and taste of goat milk, which are generally rejected by the consumer, were significantly benefited by both the jelly and L. mucosae, indicating that probiotic yoghurts added with mixed jelly have market potential and are excellent accepted food options by the consumer.